One Film, Many Perspectives: Understanding The Issue Of Climate Change In The Documentary Film Before The Flood - Mohamad Rosyidin; Ayu Sabrina; Indra Kusumawardhana (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
There have been abundant literature concerning movies as a learning tool in International Relations (IR). The use of movies as a learning tool matters in order to achieve learning outcomes since movies could reduce the level of abstraction of a concept. This paper aims to explain the global climate change phenomenon depicted in a documentary film entitled Before the Flood using four main theoretical approaches in IR, namely, realism, neoliberal institutionalism, Marxism, and constructivism. This paper argues that Before the Flood is quite relevant and effective to achieve learning outcomes of IR theories course. Watching documentary films is expected to enrich learning methods in IR particularly IR theories courses by using audio-visual instruments.